First detection and characterization of genetically divergent canine calicivirus strains in domestic dogs in China - Sihan Li; Liangyu Chu; Yancheng Zhang; Yaxuan Yu; Guoqing Wang (Frontiers in Veterinary Science)
Canine calicivirus (CaCV) belongs to the Caliciviridae family, which invades multiple host species. Notably, there are distinct serological and genetic differences between CaCV and other caliciviruses. However, the genome data for only 13 strains of CaCV have been recorded. Moreover, there have been no reports on the CaCV genome in China. To understand the genetic characteristics of CaCV in China, this study tested CaCV in 52 canine nasal swab samples by RT–PCR and finally determined that two samples were positive for this virus. The complete genome sequences of both CaCV strains were obtained through sequencing, with a genomic length of 8,453 bp. The genomic sequences of the two Chinese CaCV strains presented 83.6% nucleotide similarity with each other but 71.6%−90.2% nucleotide similarity with previously reported CaCV strains, indicating that these two CaCV strains were genetically divergent. The subsequent sequence analysis indicated that these two strains possessed unique nucleotide sites in their genomic sequences. Phylogenetic analysis revealed that the Chinese CaCV strains belonged to different evolutionary branches. Overall, the present study provides new knowledge on the prevalence and genetic diversity of CaCV in China.